2014
DOI: 10.2174/1385272819666140514005254
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry of Confined Spaces

Abstract: The reactivity in the confined spaces of zeolites, metal-organic frameworks , cage compounds and macrocycles differ in many aspects from those conducted in bulk solution. Cases of altered regioselectivity, enhanced stability and accelerated substrate reactivity are presented within the context of non-covalent interactions between host and guest molecules, which define much of supramolecular chemistry, being unique and imparting highly useful properties that are of interest for their intellectual merit as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…As already demonstrated, the zeolite catalyst employed here contains copper(I) ions and despite catalysis under air or dioxygen, these ions mostly remain at that oxidation state . This is further confirmed here by the one‐pot azidation‐click reaction, for which the click step requires copper(I) species .…”
Section: Resultssupporting
confidence: 82%
“…As already demonstrated, the zeolite catalyst employed here contains copper(I) ions and despite catalysis under air or dioxygen, these ions mostly remain at that oxidation state . This is further confirmed here by the one‐pot azidation‐click reaction, for which the click step requires copper(I) species .…”
Section: Resultssupporting
confidence: 82%
“…When the space surrounding molecules becomes restricted, their reactivity and related behavior will be altered. 695,696,698,862,863 Owing to confinement effects imparted by CNT, it has been shown that novel and distinct physical and chemical properties are found for the confined species. There have been only a limited number of studies to illustrate the use of the inner space of CNT to control noncatalytic chemical reactions.…”
Section: Confinement Effectsmentioning
confidence: 99%
“…The effects of confinement in heterogeneous catalysis have been the subject of particular attention since they can affect catalyst activity, selectivity, but also stability. , Although the majority of the studies are dealing with confinement effects in oxides, and particularly zeolites, ,, including 2D zeolites, carbon materials have also been the subject of studies, and particularly CNT. Indeed, they constitute an ideal support to study confinement effects due to (i) their specific morphology with a well-defined nanometer-size inner cavity and (ii) the possibility to deposit quite selectively the active phase either on the outer- or on the inner-surface.…”
Section: Why Anchoring Metal Nanoparticles Clusters or Metal Single A...mentioning
confidence: 99%
“…As the nanosize and quantum confinement effect in physics and material science has been well understood and established, study of anomalous physicochemistry in confined chemical nanospace started to burgeon in recent years . A prototype in this field is known as metal–organic cages (MOCs) with well‐defined nanoscopic shape and size, which are initially regarded as mimics of natural enzymes and photosynthetic processes .…”
Section: Figurementioning
confidence: 99%